Analysis of Spatial Distribution of Peatland Depth in Sumber Bakti Village - Anna Farida; Ashabul Anhar; Ali M Muslih; Hairul Basri; Teti Arabia; Ulfa Hansri Ar-Rasyid; Gita Phonnasari Jasman; Norwahyudi (Politeknik Pertanian Negeri Samarinda, 2025)
Peatland is an ecosystem formed by the accumulation of biomass that takes place faster than the rate of decomposition. In Aceh Province, the area of peatland is recorded at 338,164 hectares. Utilization of peatland that is not in accordance with the principles of sustainability can cause ecosystem degradation characterized by a decrease in the thickness and depth of the peat layer. This study aims to identify changes in the distribution of peat depth classes and analyze changes in the classification of peat ecosystems in Sumber Bakti Village. The analysis was conducted by comparing the peat depth map published by the Ministry of Environment and Forestry in 2019 with the results of spatial interpolation using the Inverse Distance Weighting (IDW) method. The research found changes in the peat depth class and variations in the extent of its distribution between the peat depth map issued by the Ministry of Environment and Forestry (KLHK) and the interpolated map in Sumber Bakti Village. In addition, a comparison of the two maps also revealed a decrease in the area of protected function areas, indicating a change in the ecological function of peatlands in the area.